2007
DOI: 10.1121/1.2799474
|View full text |Cite
|
Sign up to set email alerts
|

Distortion product otoacoustic emissions: Cochlear-source contributions and clinical test performance

Abstract: It has been proposed that the clinical accuracy of distortion product otoacoustic emissions (DPOAEs) is affected by the interaction of distortion and reflection sources contributing to the response. This study evaluated changes in dichotomous-decision test performance and threshold-prediction accuracy when DPOAE source contribution was controlled. Data were obtained from 205 normal and impaired ears with L 2 ranging from 0 to 80 dB SPL and f 2 = 2 and 4 kHz. Data were collected for control conditions (no suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 59 publications
(96 reference statements)
6
66
2
2
Order By: Relevance
“…This implies that our prediction errors may potentially be reduced by accounting for DPOAE fine structure and removing the reflection component using methods for DPOAE source separation such as time windowing (e.g., Kalluri and Shera, 2001) or selective suppression (e.g., Dhar and Shaffer, 2004;Johnson et al, 2006b). However, it is difficult to select a suppressor tone that will sufficiently suppress the DPOAE reflection component without having adverse effects on the distortion component (Dhar and Shaffer, 2004;Johnson et al, 2007), and (Johnson et al, 2007). Statistically significant correlations between measured and predicted CLS functions and simple linear regressions with slopes close to one were obtained during the training stage of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that our prediction errors may potentially be reduced by accounting for DPOAE fine structure and removing the reflection component using methods for DPOAE source separation such as time windowing (e.g., Kalluri and Shera, 2001) or selective suppression (e.g., Dhar and Shaffer, 2004;Johnson et al, 2006b). However, it is difficult to select a suppressor tone that will sufficiently suppress the DPOAE reflection component without having adverse effects on the distortion component (Dhar and Shaffer, 2004;Johnson et al, 2007), and (Johnson et al, 2007). Statistically significant correlations between measured and predicted CLS functions and simple linear regressions with slopes close to one were obtained during the training stage of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Tools have been developed for removing and/or evaluating the component from the generator region independently from the component from the DP region. One such procedure places suppressor tones near the DP frequency with the intent to suppress the component from the DP place while leaving the generator component unchanged ͑Heitmann et al, 1996;Johnson et al, 2007;Konrad-Martin et al, 2002;KonradMartin et al, 2001;Mauermann and Kollmeier, 2004;Plinkert et al, 1997͒. Unless one has some idea of the relative amplitudes of the two components, this may sometimes increase the fine structure instead of reducing it ͑Talmadge et al, 1999͒.…”
Section: Introductionmentioning
confidence: 96%
“…doi:10.1016/j.heares.2009.02.008 Wagner et al, 2008;Xu and Li, 2005). In adults, the presence of hearing loss on audiograms is usually associated with low or absent DPOAEs (Cianfrone et al, 2000;Gorga et al, 1999;Harris, 1990;Johnson et al, 2007;Nagy et al, 2002;Sisto et al, 2007;Stover et al, 1996;Wagner et al, 2005). In some studies, normal hearing subjects have been demonstrated to have reduced DPOAEs (Job and Nottet, 2002;Lutman and Deeks, 1999;Shiomi et al, 1997) compared to others, and the physician did not have an appropriate scientific method of deciding if their DPOAE results could reveal a vulnerability that could lead to a more rapid decrease of hearing capabilities.…”
Section: Introductionmentioning
confidence: 99%